Combining external physical stimuli and nanostructured materials for upregulating pro-regenerative cellular pathways in peripheral nerve repair - Redolfi Riva, Eugenio; Özkan, Melis; Stellacci, Francesco; Micera, Silvestro (Frontiers in Cell and Developmental Biology, 2024)
Peripheral nerve repair remains a major clinical challenge, particularly in the pursuit of therapeutic approaches that ensure adequate recovery of patient’s activity of daily living. Autografts are the gold standard in clinical practice for restoring lost sensorimotor functions nowadays. However, autografts have notable drawbacks, including dimensional mismatches and the need to sacrifice one function to restore another. Engineered nerve guidance conduits have therefore emerged as promising alternatives. While these conduits show surgical potential, their clinical use is currently limited to the repair of minor injuries, as their ability to reinnervate limiting gap lesions is still unsatisfactory. Therefore, improving patient functional recovery requires a deeper understanding of the cellular mechanisms involved in peripheral nerve regeneration and the development of therapeutic strategies that can precisely modulate these processes. Interest has grown in the use of external energy sources, such as light, ultrasound, electrical, and magnetic fields, to activate cellular pathways related to proliferation, differentiation, and migration. Recent research has explored combining these energy sources with tailored nanostructured materials as nanotransducers to enhance selectivity towards the target cells. This review aims to present the recent findings on this innovative strategy, discussing its potential to support nerve regeneration and its viability as an alternative to autologous transplantation.